MEMBANGUN MINAT KARIER SEBAGAI KONSULTAN PAJAK: TINJAUAN ATAS PERSEPSI, MOTIVASI, DAN LITERASI PAJAK MAHASISWA AKUNTANSI PADA UNIVERSITAS BINA BANGSA - Nurjanah, Siti; Nopianti, Rina; Pertiwi, Sari Putri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to analyze the influence of perception, motivation, and tax knowledge on accounting students' interest in becoming tax consultants. The research employed a quantitative method with a survey approach. The population comprised all 134 sixth- and eighth-semester taxation students at Bina Bangsa University, who served as the sample using a saturated sampling technique. Data analysis was performed using multiple linear regression with SPSS version 25 software. The results indicate that, both partially and simultaneously, the variables perception, motivation, and tax knowledge have a positive and significant influence on accounting students' interest in pursuing a career as a tax consultant.